Risk Analysis of Musculoskeletal Disorders Complaints Among Online Motorcycle Drivers - Pratiwi, Anisa Syafa; Widjasena, Baju; Jayanti, Siswi (Disease Prevention and Public Health Journal, 2024)
Background: Musculoskeletal Disorders (MSDs) are disorders in muscles, tendons, ligaments, joints, peripheral nerves, and blood vessels characterized by very mild complaints to very painful complaints. MSDs are caused by several factors, including work posture, work duration, vibration, and occupational stress. Work activities in online motorcycle drivers require drivers to perform static work postures with long duration, which results in the risk of MSDs complaints. This research aims to analyze the risk of MSDs complaints in online motorcycle taxi drivers in Depok City. Method: The method used in this research is the analytic method with a cross-sectional approach. The population was all online motorcycle taxi drivers in Depok City, with a sample of 40 respondents using the linear time function method. The instruments of this research were the Quick Exposure Check (QEC) questionnaire to determine work posture, work duration, vibration, and occupational stress, and the GOTRAK complaint questionnaire in SNI 9011:2021 to determine the risk of musculoskeletal complaints. Results: The results showed that 90% of online motorcycle taxi drivers experienced MSDs complaints in the upper body, with the hand being the most complained part. A correlation test using Kendall’s tau-b showed that there is a significant relationship between work duration (p=0.048), and occupational stress (p=0.032) with the risk of MSDs complaints. In contrast, work posture (p=0.299) and vibration (p=0.488) have no significant relationship with the risk of MSDs complaints. Conclusion: Work duration and occupational stress are related to the risk of MSDs complaints.